Strategic Impact of the Marketing Triangle on Building and Sustaining Successful Brands through Innovativeness and Creativity: A Balanced Perspective - Selvarajan, P. (Faculty of Management and Finance, University of Colombo, Sri Lanka., 2011)
This paper reviews the importance of branding in marketing organizations. When making a purchase, a customer is influenced by a whole range of factors associated with the complete product offer. One of these is the “brand name”. Branding of a product is very important and several factors influence that. Identifying these factors and building successful brands is really a challenge for marketers. Several researchers have suggested different methods for building successful brands. In this paper the researcher applies the concept of marketing triangle as a strategic tool and argues that there must be a balanced relationship among the employees, customers and the company to build a successful brand. Further, she proposes a conceptual framework for successful brand building and enhancing the corporate identity through employees’ innovativeness and creativity.
Keywords: Successful Brands; Innovativeness; Creativity; Customer Perception; Corporate Identity